Takhrij and Syarah Hadith of Chemistry: Benefits of Honey for Health in the Study of Hadith and Chemical Perspective - Dini Fujianti; Muhammad Daffa; Wahyudin Darmalaksana; Vina Amalia; Izzah Faizah Siti Rusydati Khaerani (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet about the health benefits of honey. This research method is qualitative through the takhrij and syarah hadith approaches with chemical analysis. The results and discussion of this study is that honey contains chemical components that are good for health. The conclusion of this research is takhrij and syarah hadith of the Prophet about honey with chemical analysis provides an understanding that the advancement of science and technology encourages Muslims to study the hadith with a scientific approach, so that several benefits of honey are found for body health and beauty.